Path Analysis of the Effect of Waist-Pelvic Circumference, Body Mass Index, and Abdominal Circumference on the Occurrence of Prediabetes - Loekito, Cindy Lestyani; Murti, Bhisma; Pamungkasari, Eti Poncorini (Indonesian Journal of Medicine, 2019)
Background: Diabetes mellitus is an important health problem in the world. Pre-diabetes is a state of blood sugar levels above normal but below the criteria for diabetes. American Diabetes Association (ADA) uses criteria for hemoglobin A1C (HbA1C) levels of 5.7% to 6.4% to define pre-diabetes. The prevalence of pre-diabetes was the highest in overweight individuals. In many studies, body fat levels were assessed by indicators of waist-pelvic circumference, abdominal circumference, and BMI. Among the three, it is still a debate which is more influential on the condition of pre-diabetes. The purpose of this study was to determine the effects of waist-pelvic circumference, BMI, and abdominal circumference in pre-diabetes.Subjects and Method: A cross-sectional study was conducted at Prodia Clinic, Surakarta, Central Java, from January to March 2019. A sample of 200 study subjects was selected by fixed disease sampling. The dependent variable was pre-diabetes. The independent variables were the waist-pelvic circumference, BMI, and abdominal circumference. The data on HbA1C was measured by NGSP standardized ion-exchange HPLC method. The data were analyzed by path analysis.Results: Abdominal circumference >90 cm in men and >80 cm in women (b= 0.87; 95% CI= 0.23 to 1.51; p= 0.008) and age ?45 years old (b = 1.70; 95% CI = 0.93 to 2.46; p <0.001) were directly increased pre-diabetes. Pre-diabetes was indirectly affected by waist?pelvic circumference, gender, and obesity.Conclusions: Abdominal circumference >90 cm in men and >80 cm in women and age ?45 years old are directly increased pre-diabetes. Pre-diabetes is indirectly affected by waist?pelvic circumference, gender, and obesity.Keywords: prediabetes, abdominal circumference, waist-pelvic circumference, body mass indexCorrespondence: Cindy Lestyani Loekito. Masters Program in Nutrition, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: cindy.l.l@student.uns.ac.id. Mobile:082134424950.Indonesian Journal of Medicine (2019), 4(3): 252-258https://doi.org/10.26911/theijmed.2019.04.03.08